A proposed model for teaching science based on the integration of constructivist learning with conceptual modeling and its effect on the depth of scientific knowledge of the sixth primary students in the Al-Baha province - Al-Ghamdi, Majed Shabab Saad (Journal of Educational and Psychological Sciences, 2019)
This study aimed to identify the effectiveness of a proposed model for teaching science based on the integration of constructivist learning with conceptual modeling and its effect on the achievement of the sixth primary students in the Al-Baha province. To achieve the goals، the research was based on the descriptive approach، and one of the semi-experimental designs was used. The research sample consisted of (46) sixth grade students in the Omar bin Abdul-Aziz School at Al-Baha Educational region، the sample was randomly divided into two groups: one experimental consisted of (22) students who studied the "power and energy" using the proposed model based on the integration between the model of structural learning and conceptual modeling، and the other 24 students who studied the unit in the traditional way، the research tool was applied to both groups، which is the depth of scientific knowledge test. The results of the post application of depth of scientific knowledge tests revealed that there were statistically significant differences at (α < 0.05) between the average degrees of the experimental group and obtained a general average (18.55 from 22) and the control group degrees and obtained a general average (11.50 of 24). And at the field of levels، the experimental obtained (6.26) in the cognitive recall، (6.90) in the application of concepts and skills، (3.14) in the strategic thinking (in exchange for the control of averages (3.52، 3.65، 3.97) respectively. The effect of the independent variable (experimental intervention) in the total degree of scientific knowledge reached 47% of the change in the performance of the experimental group in this variable. In the light of the results، a number of recommendations and suggestions were presented to disseminate the model and benefit from it in the Kingdom’s schools.